Law Enforcement of Narcotics and Prohibited Drugs Among Youth that Impact on State Security and Sovereignty - Sri Mulyani Putri Jayanti; Yusuf Saefudin (UM Purwokerto Press, 2023)
Cases of narcotics and drug abuse in Indonesia are increasingly worrying, this can be seen from the increasing number of narcotics use among the next generation of the nation, especially